Study of Drugs: Antibiotic and Study Mechanism and Adverse Effects - K. Hussein, Haider; A. Abdel Jabbar, Ban; S. Amin, Seenaa; A. Jawad, Asmaa; K. Abbas, Ruqaya; A. Jawad, Shaymaa (Al-Nahrain Journal of Science, 2023)
A drug is any chemical substance that causes a change in an organism's physiology or psychology when consumed. Antibiotics are medicines that fight bacterial infections in people and animals. They work by killing the bacteria or by making it hard for the bacteria to grow and multiply. The antibiotic can class according to structure or action or basic. Every drug have side effects on body if use If taken incorrectly.